THE EFFECT OF TEXT TWIST GAME ON STUDENTS’ VOCABULARY MASTERY AT MAS MUHAMMADIYAH 13 SEI RAMPAH - Iskandar Zulkarnain; Sofia Idawati Lubis; Jurmiani Harahap (Pedagogi: Jurnal Ilmiah Pendidikan, 2022)
The objective of this research was to know whether there is a significant effect of Text Twist Game toward students' English vocabulary mastery at MAS Muhammadiyah 13 Sei Rampah academic year 2020-2021. The research methodology applied was quasi experimental design. In this research, the population was the tenth grade students of MAS Muhammadiyah 13 Sei Rampah. The sample consisted of two classes, namely experimental class consisting of 18 students and control class consisting of 18 students. In experimental class, Text Twist Game was used to teach vocabulary while in control class was applied translation technique. The treatments were held in 3 meetings for each class. In collecting the data, the instrument used was in the form of multiple choice questions which had been tried out before the treatment. The instrument was given in pre-test and post-test. The data obtained were analyzed using SPSS to compute independent sample t-test. Based on the data analysis computed by using SPSS, it was obtained that Sig.= 0.000 and α = 0.05. It means Ha was accepted because Sig.< α = 0.000< 0.05. Therefore, it was concluded that there was a significant effect of Text Twist Game towards students’ vocabulary mastery of English of the tenth grade students at MAS Muhammadiyah 13 Sei Rampah.